Abiotic stress on seed germination and plant growth of Zeyheria tuberculosa - de Medeiros, Robson Luis Silva [UNESP]; de Paula, Rinaldo Cesar [UNESP]; de Souza, João Vitor Oliveira [UNESP]; Fernandes, João Pedro Peixoto [UNESP] (Springer Nature, 2023)
Zeyheria tuberculosa (Vell.) Bureau ex Verl. is among the Brazilian flora threatened with extinction. It has high-quality wood and can be used to recover herbicide-contaminated areas. However, abiotic stresses can harm seed germination and seedling development under adverse conditions and need to be understood to improve autochthonous or indigenous biodiversity conservation and strengthen reforestation projects. This study evaluated the effects of temperature, water and saline stress on Z. tuberculosa seed germination and water stress on seedling growth. Three laboratory experiments evaluated germination under: (1) different temperatures (20, 25, 30, 35 and 40 °C); (2) different water potentials simulated with polyethylene glycol (PEG 6000) at 25 and 30 °C; and, (3) different osmotic potentials simulated with NaCl at 25 and 30 °C. In addition, a greenhouse experiment subjected seedlings to five water regimes (20%, 35%, 50%, 65% and 80% of maximum substrate water holding capacity). In the laboratory, seedling biometry and germination were evaluated, while physiological and morphological parameters were assessed in the greenhouse. Physiological potential of seeds increased at 25 and 30 °C. Germination and vigor decreased as water and saline stresses increased. Germination tolerance thresholds for water and salt stresses were − 0.6 and − 0.4 MPa, respectively. In the greenhouse, the most restrictive water regimes reduced seedling physiological and morphological parameters. Seedling development was compromised at moisture levels below 50% field capacity.
Keywords: Bignoniaceae; Climate change; Ipê-felpudo; Ipê-preto; Water stress